THE EFFECT OF FINANCIAL PERFORMANCE ON THE STOCK PRICE OF COMPANIES WITH EARNINGS PER SHARE AS A MODERATING VARIETY (CASE STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX IN 2019-2023) - Arya Permana Ginting; Rico Nur Ilham; Ghazali Syamni; Chairil Akhyar (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This research aims to determine the effect of financial performance on company share prices with earnings per share as a moderating variable (case study of property and real estate companies listed on the BEI in 2019-2023. The sample for this research is 52 property and real estate sector companies listed on Indonesia Stock Exchange (BEI) and which submitted consecutive annual financial reports during the 2019-2022 period. The analysis tool used is panel data regression using descriptive statistics, classical assumption tests and hypothesis testing has no effect on share prices in property and real estate sector companies listed on the BEI for the 2019-2023 period, then EPS is unable to influence ROA and DER on share prices in property and real estate sector companies listed on the BEI for the 2019-2023 period.